European cultures of sport : examining the nations and regions - Riordan, James, 1936-2012; Krüger, Arnd (Intellect, 2003)
Sport occupies a key position in the cultural profile of a nation. This study forms a comparative guide to sport across Europe, in terms of its relative political and social status, its development, and the ways in which it has contributed to national achievement. Covering sport in ten major European states, each native contributor to the study presents: a brief historical background: major sports successes, Olympic positions, sporting traditions, organisation of sport: its structure and financing, elite sport: how talent is spotted, nurtured and remunerated, sports academies, national qual.